Characteristics of International Relations Postgraduate Program Graduates - Fonseca Hernández, Raúl Gerardo (2019)
The objective of this study is to identify characteristics of current students, graduates and former students who dropped out of International Relations graduate programs in Costa Rica in terms of future job placement and better understand the weight of this area of study in Costa Rica compared to other disciplines. The results included a combination of surveys completed by both students and employers which, after a statistical analysis, conclude that younger students tend to consider this type of postgraduate program more attractive. Many of these students are employed full time or more and most work within the private sector. Significant variables associated with students that complete and graduate from these programs, such as gender, educational background, labor sector (public or private), age and where a person resides. It is concluded that a master’s degree in International Relations is an attribute that makes an individual more marketable. Yet, universities must strive to include soft skills development in the study plans required for today´s job market.